The impact of Korea's exchange rate volatility on Malaysia's trade and foreign direct investment / Mohd Asri Syahrol - Syahrol, Mohd Asri (2008)
This paper empirically describes Korea's exchange rate volatility and its impact on Malaysia's trade and foreign direct investment. The paper will concentrate on the trade and investment of Malaysia in relation with Korea's exchange rate for the period of 11 years from the year 1997 to 2007. In the study, Granger Causality model are used to explain the relationship and the impact between independent and dependent variables. Granger causality is a technique for determining whether one time series is useful in forecasting another. The paper show that only certain period that volatility in Korean exchange rate Granger cause the dependent variable of trade and also the foreign direct investment exchanges between the two countries. In addition, the paper provides evidence that exchange rate volatility does not have robust and significant impact to trade and foreign direct investment inflows. It will show that greater volatility of exchange rate does not lead to a decreased trade and foreign direct investment. Exchange rate of Korea is used as the independent variable while Malaysia's trade and foreign direct investment acts as the dependent variable.